Population reinforcement accelerates subadult recruitment rates in an endangered freshwater turtle. (19th April 2019) - Carstairs, S.; Paterson, J. E.; Jager, K. L.; Gasbarrini, D.; Mui, A. B.; Davy, C. M.
Abstract: Wildlife diversity and abundance are declining globally and population reinforcement with captive‐reared animals is a common intervention used to prevent extinctions. Released captive‐reared individuals may undergo an acclimation period before their behavior and success is comparable to wild‐reared individuals because they lack experience with predators, complex habitats and variable environmental conditions. Quantifying post‐release acclimation effects on fitness and behavior is important for maximizing the success of reintroduction programs and for predicting the number of captive‐reared animals required for release. Endangered Blanding's turtles Emydoidea blandingii exhibit low recruitment and may benefit from population reinforcement with captive‐reared, 'headstarted' individuals (headstarts). We used 6 years of data to compare survival, growth, habitat use and movement ecology between wild‐hatched juvenile turtles and headstarts reared from eggs rescued from injured females. We found strong evidence of an acclimation effect in headstarts, with lower movement, growth, and survival during the first one to two years post‐release. Following this acclimation period, headstarts had movement, growth and survival similar to wild‐hatched juveniles. Habitat use did not differ between headstarts and wild‐hatched juveniles. We hypothesize that the acclimation period occurred because headstarts were introduced directly into the wild (i.e. 'hard release') and that providing additional support before or after release may improve the success of headstarts. Headstarts had a monthly survival probability of 0.89 in the first year post‐release, and 0.98 after the first year post‐release. We estimated that headstarts at our sites have approximately three times higher probability of surviving to 10 years of age, compared to wild‐hatched individuals at other sites. Our results highlight that headstarts should be released into habitat individually rather than in clusters, and highlight the need to investigate whether post‐release mortality of captive‐reared animals could be mitigated by increased acclimation to wild conditions, for example through prerelease periods in outdoor pens. Abstract : Releasing captive‐reared animals (headstarts) can increase recruitment in endangered species, but programs are rarely evaluated with comparisons to wild animals in the same population. By comparing the fitness and behavior of headstarts to wild‐hatched juveniles of Blanding's turtles, we found that after a brief acclimation period, headstarts had similar survival, growth, and movement rates to wild‐hatched juveniles.